Praktik Identitas Panggung Sri Mules sebagai Strategi Cultural Branding dalam Pertunjukan Dangdut Pantura - Hasbil Haqqy Arif; Moh. Muttaqin (Lembaga Pengembangan Kinerja Dosen, 2026)
This study analyzes the stage identity practices of the dangdut music group Sri Mules as a cultural branding strategy in Pantura dangdut performances. In contrast to common dangdut performance patterns that position the singer as the primary visual focus, Sri Mules adopts a performative approach that foregrounds accompanying musicians as the main visual actors through the use of unconventional costumes and collective stage actions. Employing a qualitative approach with a case study strategy, this research draws on visual documentation of performances circulated on social media during the group’s active phase (2020–2021), complemented by semi-structured interviews and reflective observations. Data were analyzed using the interactive model proposed by Miles and Huberman, informed by performance theory (Schechner) and the concept of cultural branding (Holt). The findings indicate that Sri Mules’ stage identity is constructed and reproduced through consistent visual deviation and collective performativity, functioning as a strategy of symbolic differentiation in the Pantura dangdut performance landscape. This study highlights the role of accompanying musicians as active agents in shaping the visual identity of dangdut performances.